STRATEGI SCRAMBLE UNTUK MENINGKATKAN KEMAMPUAN KERJASAMA SISWA KELAS II SD NEGERI 0507 LATONG - Masripa Salimah Hasibuan; Lailan Aprina Siregar, Era Mutiah (Adisam Publisher, 2024)
The purpose of this research is to determine (1) the cooperation ability of grade II students of SD Negeri 0507 Latong. (2) Scramble strategy in improving cooperation between grade II students of SD Negeri 0507 Latong. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles where each cycle consists of planning, implementation, observation and reflection. This research was carried out in grade II SD Negeri 0507 Latong, The source of data in this study was divided into two, namely (1) primary data, namely grade II students of SD Negeri 0507 Latong, (2) secondary data, namely grade II teachers of SD Negeri 0507 Latong. Data collection techniques in this study were obtained through observation, written tests and documentation. Data analysis techniques in this study are qualitative data analysis techniques. Based on the results of the study, it can be concluded through the pretest that the cooperation ability of grade II students of SD Negeri 0507 Latong is still low There were 7 students or 17.95% in the